2004
DOI: 10.1177/0730888403260734
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Occupational Characteristics on the Experience and Expression of Anger in the Workplace

Abstract: This article examines the relationships among extensive interaction with others on the job, occupational status, and the experience and expression of anger in the workplace using data from the 1996 General Social Survey and occupational characteristic measures from the Dictionary of Occupational Titles. The findings indicate that individuals who spend much of their time interacting with others at work report experiencing workplace anger more frequently than other workers. The expression of anger was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 39 publications
5
110
1
6
Order By: Relevance
“…Still, despite their age and experience, the majority of respondents were relatively low level employees. Thus our findings are similar to those of previous studies, which have suggested that low level employees are likely to be required to perform more emotional labor (Leidner, 1999;Sloan, 2004).…”
Section: Table 4 To Feature Heresupporting
confidence: 92%
See 1 more Smart Citation
“…Still, despite their age and experience, the majority of respondents were relatively low level employees. Thus our findings are similar to those of previous studies, which have suggested that low level employees are likely to be required to perform more emotional labor (Leidner, 1999;Sloan, 2004).…”
Section: Table 4 To Feature Heresupporting
confidence: 92%
“…In particular, studies have suggested that greater emotional labor demands are placed on women (Guy & Newman, 2004), and that employees in lower status positions, or even professionals whose emotional labor is monitored by their superiors, will face more emotional labor demands or emotional dissonance (Leidner, 1999;Sloan, 2004). To the extent to which age and experience are discussed, research tends to suggest that younger and less experienced employees are less likely to be able to effectively manage their emotions or engage in deep acting (Dahling & Perez, 2010;Erickson & Grove, 2007;Hochschild, 1983).…”
Section: The Consequences Of Emotional Labormentioning
confidence: 99%
“…The module also asked a series of more detailed questions about respondents' experience of anger, including questions about the target of their anger, who bore most responsibility for its provocation, and how they coped with this emotion. Sloan (2004) used these data to test hypotheses about the relations between anger and employment in a people-intensive occupation. As expected, those employed in jobs requiring high levels of contact with people reported experiencing more anger at work than those in less peopleintensive occupations.…”
Section: The Example Of Angermentioning
confidence: 99%
“…Research suggests that perceived emotional support from coworkers is directly associated with higher levels of happiness and lower levels of negative emotions and depressive symptoms (Loscocco and Spitze 1990;Menaghan 1991;Pugliesi 1995;Sloan 2012;Turner and Marino 1994). Furthermore, coworkers can provide support for one another in dealing with work-related emotional experiences, including emotional labor that workers perform for others while on the job (Korczynski 2003;Lively 2000) and feelings of anger toward another individual in the workplace (Lively and Powell 2006;Sloan 2004). Although substantial evidence suggests that social ties and social support are beneficial, these resources are not distributed equally in the population (McPherson, Smith-Lovin, and Brashears 2006;Schieman 2005;Umberson and Montez 2010).…”
Section: Social Relationships In the Workplacementioning
confidence: 99%